Risk factors for unsatisfactory colposcopy after large loop excision of the transformation zone: The results of a four-year multicenter prospective study. (September 2019) - Chevreau, Julien; Carcopino, Xavier; Foulon, Arthur; Preaubert, Lise; Lanta-Delmas, Ségolène; Sergent, Fabrice; Gondry, Jean
Abstract: Objectives: Not being able to completely examine the cervical squamocolummar junction (SCJ) in colposcopy after large loop excision of the transformation zone (LLETZ) is an important issue regarding surveillance, as high-grade cervical intra-epithelial neoplasia recurrence risk is high. This study was conducted in order to identify risk factors for post-LLETZ unsatisfactory colposcopy. Methods: This prospective multicenter observational study was performed in nine French University hospitals, with inclusions running from December 2013 to December 2017. All patients scheduled for LLETZ were included and were divided into two groups after the two to four months post-procedure colposcopic examination: a satisfactory and an unsatisfactory post-LLETZ colposcopy group. Results: In total, 601 cases were analyzed and 71 post-LLETZ colposcopies (12%) were described as unsatisfactory (including 19 cervical stenosis). In a univariate analysis, we only observed a statistically significant increase of the following parameters in the unsatisfactory post-LLETZ group in comparison with the satisfactory post-LLETZ group: parity (2.11 [±1.55] and 1.49 [±1.24] respectively, p < .01), depth of the LLETZ specimen (10.9 mm [±3.37] and 9.76 [±3.79] respectively, p < .01), age (45.9 years [±11.7] and 37.9 [±9.42] respectively, p < .001) and an unsatisfactory pre-LLETZ colposcopy (43 satisfactory pre-LLETZ colposcopies [61%] and 456 [86%] respectively, p < .001). In a stepwise binary logistic regression analysis, only the two latter parameters were found to be independently associated with unsatisfactory post-LLETZ colposcopies. Conclusions: Surgeons should consider other therapeutic strategies when contemplating iterative diagnosis-LLETZ in older women with initially invisible SCJ, as an appropriate post-LLETZ surveillance is at higher risk of being impossible to achieve.